Social Development Through Participatory Dakwah Approach - Azwar, Welhendri (Universitas Islam Negeri Imam Bonjol Padang, 2005)
his article explains unsatisfied conventional-positivist paradigm that brings allernate partisipative paradigm in order to solve social problems. The writer explains about PRA (Participatory Rural Appraisal). PRA is a method in understanding (rural) society, from, for and with the society itself. This method includes analysis, plan action, and also monitoring and evaluating the program social development Partisipative method (PRA) brings empowerment. Every body has the right to say what they have in their mind in order lo get deosion reiated to ther life.